Effective doses of remimazolam and esketamine combined with remifentanil for endotracheal intubation without muscle relaxants in pediatric patients - Chen, Jinming; Mai, Ying; Cheng, Xiaolei; Sun, Hao; Chen, Zhihong; Zhang, Zhongqi (Frontiers in Pharmacology, 2025)
IntroductionThe combination of remimazolam and esketamine effectively alleviates adverse hemodynamic effects, such as tachycardia and hypertension, during intubation. However, the dosage for achieving optimal intubation conditions when co-administered with remifentanil remains unestablished. Therefore, this study aimed to determine the effective doses of remimazolam and esketamine for endotracheal intubation without muscle relaxants in pediatric patients using Dixon’s up-and-down method.MethodsThis prospective, non-controlled, non-randomized clinical trial sequentially allocated 41 children aged 3–6 into two phases. All patients underwent tracheal intubation under general anesthesia. Patients received a fixed dose of remifentanil at 2.5 μg/kg via a pump over 90 s. In the first phase, the induction dose of remimazolam was set at 0.2 mg/kg. The first patient received esketamine at a dose of 0.5 mg/kg, administered with a dose gradient of 0.2 mg/kg based on Dixon’s up-and-down method. 50% effective dose (ED50) and 95% effective dose (ED95) for esketamine were then measured through probit regression analysis. Similarly, in the second phase, the ED95 of esketamine was fixed. The first patient received remimazolam at a dose of 0.2 mg/kg, administered at a dose gradient of 0.1 mg/kg. ED50 and ED95 for remimazolam were then measured. Intubation conditions were assessed via the Copenhagen scale. Heart rate (HR) and mean arterial pressure (MAP) were recorded at the following time points: Just before intubation (T1) and 1 min after intubation (T2). Adverse events were also recorded during anesthesia induction.ResultsAt a fixed dose of remifentanil (2.5 μg/kg), the ED50 of esketamine was 0.74 mg/kg (95% confidence interval [CI]: 0.61–0.89 mg/kg), while the ED95 was 0.97 mg/kg (95% CI: 0.85–1.75 mg/kg). The ED50 of remimazolam was 0.39 mg/kg (95% CI: 0.29–0.53 mg/kg), while the ED95 was 0.56 mg/kg (95% CI: 0.46–1.47 mg/kg). Hemodynamic stability was maintained during anesthesia induction, with no significant adverse events observed.ConclusionThe ED50 and ED95 values of remimazolam and esketamine in this study provide initial dosing references for pediatric endotracheal intubation without muscle relaxants. A fixed dose of 2.5 μg/kg remifentanil combined with these agents is safe and effective in children aged 3–6 years, though further multicenter studies are recommended for validation.Clinical trial registrationwww.chictr.org.cn, number: ChiCTR2200063847.